Demonstration of axon reflexes in human motor nerve fibres - Stålberg, E. (1970)
Responses of single muscle fibres to electrical stimulation of the tibial nerve trunk or of the intramuscular nerve twigs were detected in young volunteers without evidence of neurological disease. With suitably adjusted amplitude of the stimulus, clear-cut double distribution of the response latencies was obtained in some fibres. Experiments with two stimulating cathodes and with recordings from more than one muscle fibre in the same motor unit suggest that axon reflexes were involved. The results indicate that axonal branching normally occurs not only in the intramuscular course of the nerve but also outside the muscle, in some cases even rather high in the nerve trunk. The possibility is discussed that axon reflexes may underlie fasciculations evoked by neostigmine and those seen in some other conditions, such as amyotrophic lateral sclerosis, as well as muscle cramps in normal subjects.